Analysis of the impact on the application of the rules governing the promotion and repetition within the public education system in the management Rican Professional Technical College of Limon - Jobson Vargas, Marlyn (2012)
The author gives a brief analysis about the impact on the application of the rules governing the promotion and repetition within the public Costa Ricaneducation system in the management of the Professional Technical College of Limon. This raises the importance of educational administration and their use as the means by which it allows the implementation of these policies and strategies that have been implemented in the institution to apply the rules granting access to students who have dropped out of education system and promoting these standards in force and repetition can retake them.